Assessment of Maximum Voluntary Ventilation (MVV) in Female Hypothyroids and Its Relationships with Serum TSH and FT4 Levels (Delta Medical College Journal, 2020)
Background: Hypothyroidism is a common hormonal disorder affecting various organs including lungs and pulmonary dysfunction in hypothyroid patients has been noted.Objective: To observe maximum voluntary ventilation (MVV) in hypothyroid female patients.Materials and method: This cross-sectional study was carried out in the Department of Physiology, BSMMU, Dhaka, Bangladesh, from 1st July 2008 to 30th June 2009 on 60 hypothyroid female patients of 30-50 years old. Based on treatment, hypothyroid patients were divided into B1 (untreated patients on their 1st day of diagnosis) and B2 (patients treated for at least 12-18 months). For comparison, 30 age and BMI matched apparently healthy subjects (Group A) were also studied. The study group was selected from the Out Patient Department of Endocrinology, BSMMU, Dhaka, Bangladesh, and the control group was selected by personal contact. Serum TSH and serum FT4 levels were measured by Microparticle Enzyme Immunoassay (MEIA) principle in AxSYM system. Maximum voluntary ventilation (MVV), which is a lung function parameter, was measured by a digital MicroDL spirometer. Data were analyzed by one way ANOVA test, independent sample t-test and Pearson’s correlation coefficient test.Results: The mean percentage of predicted values of lung function parameter of MVV in control subjects and treated hypothyroids were within normal ranges. However, this value was significantly lower in untreated hypothyroid subjects in comparison to those of control and treated hypothyroid subjects. In addition, MVV showed negative correlation with serum TSH level and positive correlation with serum FT4 level and these relationships were statistically significant in control group and treated hypothyroid subjects.Conclusion: This study reveals that MVV may be lower in untreated hypothyroid female patients compared to control and treated hypothyroids and the deterioration may be positively correlated with serum FT4 level and negatively correlated with serum TSH level. Treatment of hypothyroids may reverse these changes.Delta Med Col J. Jul 2020;8(2): 55-60